Migration intentions in Selangor, Malaysia: A descriptive analysis / Azreen Anuar ... [et al.] - Anuar, Azreen; Mohd Hussain, Nur Huzeima; Mohd, Thuraiya; Masrom, Suraya; Ahmad, Suriati (2022)
The present study attempts to examine the current migration intentions of the urban migrants in Selangor, Malaysia using data from the Department of Statistics Malaysia 2018. Migration is crucial to population redistribution and development in Malaysia. It is instrumental in the redistribution of human resources and productivity improvements. In particular, this paper identifies the respondents' background including gender, employment, occupation, ethnic group, marital status, education profiles, and migrations' intention. By using 425 sample size data from the Department of Statistics Malaysia, these data are analyzed using a descriptive analysis method. The descriptive analysis described the data between the internal migrants as the dependent variable with the migration intention factors. Therefore, this paper presents the significant factors that contribute and play essential roles in the migration intention of the urban migrants in Selangor, Malaysia. Consequently, the findings have revealed career reasons and following family driving factors for people to migrate from urban to rural migration. Career and environment reasons for people from urban to rural migration in Selangor, Malaysia. This research is significant for predicting future trends and needs in population migration in Selangor, Malaysia.